Eyetracking evidence for heritage speakers’ access to abstract syntactic agreement features in real-time processing - Fuchs, Zuzanna (Frontiers in Psychology, 2022)
This paper presents the results of an eyetracking study that uses the Visual World Paradigm to determine whether heritage speakers of Polish can use grammatical gender cues to facilitate lexical retrieval of the subsequent noun during real time processing. Previous work has investigated this question for heritage speakers of Spanish with gender cues located on definite articles, which are highly frequent in Spanish; the results are therefore consistent both with a grammatical account, wherein heritage speakers access abstract syntactic gender features during processing, and a probabilistic account, wherein facilitation is due to transition probabilities between frequently co-occurring elements. In Polish, gender cues appear on adjectives, which are optional and infrequent. Results of the present study show that heritage speakers of Polish can use gender on inflected adjectives to fixate on the target noun faster in trials where that gender cue uniquely identifies the target noun. This finding supports a grammatical rather than probabilistic account of the facilitative use of grammatical gender in this population: heritage speakers are able to access abstract syntactic information in real time to aid word recognition in a target-like manner.